Construction and validity of the Malice Scale in university students from Lima - Cárdenas, Cynthia (2023)
Introduction: Evil is present in people’s behavior, therefore, it constitutes an indispensable subject of study for psychology to study it in order to evaluate and understand the damage it can cause to many individuals. Objective:To construct an instrument to measure malice, malevolence or meanness identifying its main psychometric properties such as validity and reliability. Material and Methods: The study was instrumental in a non-probabilistic sample, through the online application of the Meanness Scale (ESMA-31) consisting of 31 items with 4 dimensions: selfishness, idealism, sadism, and omission of help. The sample consisted of 403 psychology students from a public university in Lima, aged between 18 and 31 years. For the construction of the scale, the 6 dimensions and 36 items of the first version were used. Results: The scale presented an omega coefficient between 0.70 and 0.74, and an ordinal alpha between 0.82 and 0.93. Regarding content validity, Aiken V values were between 0.89 and 1.00, p = 0.001. Confirmatory factor analysis evidenced four dimensions with adequate fit indices [χ2/gl = 2, SRMR = 0.064, CFI = 0.955, TLI = 0.951 and RMSEA = 0.054]. Conclusions: The instrument presents evidence of content and internal structure validity, in addition to adequate internal consistency of scores